Zoneamento e mapeamento geoambiental no município de Sorriso - MT - Cabral, Tiéle Lopes (2014)
The action of man over nature manifests itself in many forms depending on the means adopted for the constant search for elements that allow for their presence in nature. Thus, the present study aims, zoning and mapping Geoenvironmental in the municipality of Sorriso - MT, in order to diagnose and assess the constraints and capabilities of the landscape opposite the occupation. Based on this goal and linked to the topic of research, geoenvironmental mapping comes assist in the study area because it allows jointly analyze information for use and occupation of the land, from the interaction of thematic maps with the support of Geographical Information System (GIS ), depicting more broadly triggering the evolution and/or degradation in certain areas of the city. Methodologically, the work is centered on the literature survey, the readings of subjects related to the central theme of the proposed research being developed at the Masters and data extracted from the GIS and fieldwork. The relevance of this issue is due to the very rapidity of the advance of agriculture in the Midwest region of Brazil that brings numerous interventions in the Cerrado environments linked to farming practices in agribusiness scale. Thus, from the perspective of Geoenvironmental approach, the analysis of landscape elements and the impact of human practices on these permits to understand how to establish social relationships with the natural substrate as a stage, even assisting in the understanding of surface dynamics in the many forms of use and occupation of the physical environment, especially in relation to primary production sector, where we observe the form of management of agricultural soil . As main results, this work shows that the sectors of greatest weaknesses are concentrated in the Dissection systems with native vegetation (riparian and gallery) and dirty fields in Quartzipsamments Cambisols and Hydromorphic, comprising an area with higher slopes, where erosion may occur and inability to agricultural use, and on the top of the Dissected Parecis Plateau where agricultural practice inserted this system, bringing a string of environmental problems. The definition of geo-environmental characteristics is fundamental for the development project planning and management that should involve society. Furthermore, this study serves as a basis for work involving different themes on a larger scale to the Plateau dissected Parecis, contributing information of a region with limited studies in the state of Mato Grosso.